EXPLORING HOW FAMILY ACCOMMODATION INFLUENCES REPETITIVE BEHAVIORS IN CHILDREN WITH AUTISM: A MIXED-METHODS STUDY - Nazima Jahangir Bhatti; Muhammad Sarwar; Muhammad Arif, (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
Diagnosis of Autism Spectrum Disorder (ASD) is significantly influenced by restricted and repetitive behaviors and interests (RRBI). These behaviors frequently pose the most substantial obstacles in the daily lives of children with ASD and their families. Nevertheless, there is a scarcity of research that examines family accommodation behaviors (FAB) within the ASD community, and the relationship between these accommodations and the specific features of the children's behaviours is as yet undecided. Utilizing a sequential mixed-methods approach, the objective of this study was to explore the connection between RRBI and FAB in order to acquire a better understanding of the lived experiences of parents with their children's RRBI. The investigation was implemented in two phases: a quantitative phase and a qualitative phase. Initially, 29 parents of autistic children aged 5–13 accomplished questionnaires. Subsequently, 15 of these parents were interviewed concerning their children's RRBI and FAB. In the qualitative phase, extensive phenomenological interviews were conducted. It was discovered that there is a robust positive association between RRBI and FAB, as well as between their sub-components. These findings were further substantiated by the qualitative data, which provided illustrative examples of the compromises that families make in order to address RRBI-related issues. Overall, the investigation underscores the significance of addressing both autism-related behaviors and the experiences of parents, as each influences and is influenced by the other, thereby emphasizing the interconnectedness of RRBI and FAB.